가변금형 성형에서 탄성회복 제어 연구 - 하석문; 박종우; 김태원 (한국소성가공학회, 2008)
Springback is one of the most difficult phenomena to analyze and control in sheet forming. Most of traditional springback control methods rely on experiences of skilled workers in industrial fields. This study focuses on prediction and generation of optimum reconfigurable die surfaces to control shape errors originated by springback. For this purpose, a deformation transfer function(DTF) was combined with finite element analysis of the springback in the 2D sheet forming model of elastic-perfectly plastic materials under the condition without blank holder. The results showed shape errors within 1% of the objective shape, which were comparable with analytically predicted errors. In addition to this theoretical analysis, DTF method was also applied to 2D and 3D sheet forming experiments. The experimental results showed ±0.5 mm and ±1.0 mm shape error distribution respectively, demonstrating that reconfigurable die surfaces were predicted well by the DTF method. Irrespective of material properties and sheet thickness, the DTF method was applicable not only to FEM simulation but also to 2D and 3D elasto-reconfigurable die forming. Consequently, this study shows that springback can be controlled effectively in the elasto-RDF system by using the DTF method.